Analysis of Factors Affecting Inter-Provincial Inequality in Java - Murniati, Neni; Gumelar, Sandi Cahaya; Ramdaniatulfitri, Intan (Jurnal Riset Ilmu Ekonomi, 2024)
This study aims to determine the characteristics of all variables during the observation period, and determine the effect of all independent variables on the level of interprovincial inequality in Java through the panel data analysis method. This study uses the Williamson Index as a parameter of interprovincial inequality. The research observed on how per capita income, population, investment, open unemployment rate, and the Human Development Index (HDI) affect the level of interprovincial inequality in Java during 2010 – 2021. The results of the study show that during 2010 – 2021 the level of interprovincial inequality in Java tends to increase significantly. Judging from the level of inequality, sequentially there are 3 provinces in Java that have the highest level of inequality, namely DKI Jakarta, Central Java and West Java. On the other hand, partially the level of per capita income, population, open unemployment rate, and HDI have a significant effect on the level of interprovincial inequality in Java, but the level of investment has no significant effect on interprovincial inequality. It was also found that partially per capita income and HDI were the two variables that most influenced the level of interprovincial inequality in Java.